2022
DOI: 10.1142/s0217979223500182
|View full text |Cite
|
Sign up to set email alerts
|

Darcy–Forchheimer flow of CNTs-H2O nanofluid over a porous stretchable surface with Xue model

Abstract: This investigation includes a three-dimensional Darcy–Forchheimer flow model and the heat transfer phenomenon of H2O-CNTs nanofluid for a two-way stretchable surface. Xue’s proposed thermal conductivity model is employed. The numerical analysis scheme is applied to solve the transformed PDEs. The outline of velocities, temperature, surface drag forces and Nusselt number against relevant variables are portrayed. From this study, it has been noted that with an increase in Eckert numbers along both directions, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To determine the unknown initial conditions k 1 , k 2 , l 1 , and l 2 , we shoot them for arbitrary slope so that the solution of the system of ODEs satisfies the boundary conditions at ∞, and its accuracy is checked by comparing the calculated quantities with the provided end points. After obtaining these values, we apply the fourth-fifth order Runge-Kutta-Fehlberg technique to solve a system of first-order ODEs in (33) with boundary conditions (34) and determine ε from (35). To get the dual solutions, we take different initial approximates for the values of k 1 , k 2 ,where all profiles asymptotically satisfy the ∞ boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the unknown initial conditions k 1 , k 2 , l 1 , and l 2 , we shoot them for arbitrary slope so that the solution of the system of ODEs satisfies the boundary conditions at ∞, and its accuracy is checked by comparing the calculated quantities with the provided end points. After obtaining these values, we apply the fourth-fifth order Runge-Kutta-Fehlberg technique to solve a system of first-order ODEs in (33) with boundary conditions (34) and determine ε from (35). To get the dual solutions, we take different initial approximates for the values of k 1 , k 2 ,where all profiles asymptotically satisfy the ∞ boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Shaw et al [34] studied the application to brain dynamics of the impact of entropy generation on the Darcy-Forchheimer flow of MnFe 2 O 4 -Casson/water nanofluid because of a rotating disk. In their recent study, Upreti et al [35] discussed the hydromagnetic stagnation point magnetite ferrofluid flow over a convectively heated shrinking/stretching permeable sheet surface which is exposed to injection/suction in a Darcy-Forchheimer porous medium. Joshi et al [36] investigated the Darcy-Forchheimer flow model in a threedimensional case and the heat transfer phenomenon of H 2 O-CNT nanofluid on a two-way stretchable surface, and it was observed that with an enhancement in the Eckert numbers along the two directions, for temperature curves, two patterns were obtained, the initial temperature outlines rose, and after that, they diminished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently many authors [38–42] have contributed towards this research work. Moreover, the development in the field has been observed by the eminent scholars [14, 43–49] which has been considered in the present study.…”
Section: Introductionmentioning
confidence: 95%
“…The effects of stress, flow, and heat transfer over a spinning disc with temperature-dependent nanofluid characteristics were examined by Upreti et al 22 . Upreti et al 23 studied the MHD flow rate of nanofluid across a porous surface using the Xue framework. Pandey et al 24 looked at the impact of spontaneous convection on the three-dimensional flow of nanostructures across porous surfaces.…”
Section: Introductionmentioning
confidence: 99%